International political economy thought in pre-modern and colonial Korea - Hyoung-kyu Chey (International Trade, Politics and Development, 2019)
Purpose – The purpose of this paper is to analyse international political economy (IPE) thought in Korea during its pre-modern and colonial eras. Design/methodology/approach – It divides these eras into three periods. The first period is the eighteenth century, in which Silhak arose. The second is the mid- and late nineteenth century, a time characterised by conflicts between Wijeong-cheoksa and Gaehwa thoughts. The final period is that of colonial Korea under imperial Japan, and during this time economic nationalist movements were pursued while Marxist theories were also introduced to the country. Findings – This research shows that IPE thoughts analogous to Western economic liberalism and economic nationalism did emerge endogenously in Korea when its environment was similar to those in which these Western thoughts arose, although in ways that reflected Korea’s peculiar situations of the times. This study also demonstrates that the “economic” thoughts of the Koreans in these periods were shaped largely by their political thoughts. Originality/value – This research contributes to the building of a more “globalised” intellectual history of classical IPE thought.